2022
DOI: 10.17235/reed.2022.8380/2021
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tofacitinib in the treatment of ulcerative colitis: real-life experience in Andalusia

Abstract: Project management, coordination, formal analysis, data preservation, first draft, revision and editing of the manuscript, methodology and research. Pilar Navajas Hernández: Data collection and preservation, revision and editing of the manuscript. María del Mar Martín Rodríguez: Data collection and preservation, revision and editing of the manuscript. Marta Lázaro Sáez: Data collection and preservation, formal analysis, first draft, revision and editing of the manuscript. Raúl Olmedo Martín: Data collection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…A single study compared steroid-free remission rates and observed no significant differences between patients exposed to biologics (48%) and unexposed patients (55%). A more recent study, in which 98.3% of patients had been exposed to biologics, confirms the efficacy of tofacitinib in a highly refractory population (37).…”
Section: Scenariomentioning
confidence: 77%
“…A single study compared steroid-free remission rates and observed no significant differences between patients exposed to biologics (48%) and unexposed patients (55%). A more recent study, in which 98.3% of patients had been exposed to biologics, confirms the efficacy of tofacitinib in a highly refractory population (37).…”
Section: Scenariomentioning
confidence: 77%
“…Previous studies also showed similar trends for biochemical improvements after tofacitinib treatment. 13 , 16 18 , 20 , 21 , 28 Previous studies have also shown that higher serum CRP and lower serum albumin levels are correlated with severe clinical and endoscopic disease activities and poor prognosis. 38 41 In addition, improvement in the serum CRP and albumin within a short period after starting the biologic treatment has been reported to be related with better outcomes for UC patients.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those of other real-world studies, which reported 0–1.3% of patients developing venous thromboembolism after tofacitinib therapy. 14 , 16 22 , 24 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…Up to now, in only one relatively small, retrospective cohort remission rates of tofacitinib in UC patients after 24 months of treatment were described. 16 In 13 patients, 53.8% were in remission after 24 months (defined as a partial Mayo score ≤2), but it was unclear whether an intention to treat analysis was used. Other studies evaluated the effectiveness of tofacitinib up to 1 year of treatment.…”
Section: Discussionmentioning
confidence: 99%